Pengaruh Diameter Lubang Nozel Terhadap Karakteristik Api Dan Waktu Pemanasan Air Pada Kompor Multifuel - Saparin, Saparin; Harahap, Fahmi; Setiawan, Yudi; Sari Wijianti, Eka; Ariksa, Jeri (Jurnal Inovasi Teknologi Terapan, 2024)
Stoves have experienced developments from time to time. One of the stove developments is a multifuel stove which is a type of stove that can use many types of fuel as fuel. Multifuel stoves have many important components that function to support the combustion process, one of which is the stove nozzle which functions to flow air into the combustion tube. In this study, tests will be conducted to find out the effect of variations in the diameter of the stove nozzle holes on the characteristics of the fire and water temperature during the water heating process. The method used in this test is a combination of experimental studies and literature studies. There are 5 variations of nozzle hole diameter that will be tested, namely 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, and 3.5 mm. The fuel used is used cooking oil. The desired fire characteristic is the longest flame length. The results of the tests that have been carried out are based on the highest average fire temperature is 716°C found in nozzles with a hole diameter of 2.5 mm, and the lowest average fire temperature is 557°C found in nozzles with a hole diameter of 1.5 mm. The longest flame duration was 1,295 seconds at the nozzle hole diameter of 1.5 mm, while the fastest flame duration was 832 seconds at the nozzle hole diameter of 3.5 mm. The variation of nozzle hole diameter has no effect on the color of the flame, which produces a blue color with a yellowish flame tongue. The longest water boiling time was 180 seconds for nozzle hole diameters of 1.5 mm, 3.0 mm, and 3.5 mm, while the fastest water boiling time was 150 seconds for nozzle hole diameters of 2.0 mm and 2.5 mm.